Kedibone - Mokae, Sabata Paul (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2014)
A young woman from a rural village near Kimberley is killed by her husband in a fit of jealousy. Her illiterate mother is summoned to the hospital to authorize the removal of vital organs "“ eyes, liver, kidney and heart "“ for organ donation. But some members of the family feel that their child should not be buried with parts of her body missing. Thus begins a story that changes the lives of many people, both black and white, over the following twenty years.
Keywords: Creative writing (Higher education) -- Research -- South Africa; Creative writing -- Fiction; South African fiction (English) -- Study and teaching (Higher); South African fiction (English) -- 21st century